The Law Of Mahar Gifts From The Perspective Of The Syafi'i And Maliki - Muchammad Luthfillah Wafi; Imron Choeri; Hudi Hudi (JURNAL HUKUM SEHASEN, 2024)
The aim of this research is to investigate and comprehend the laws and practices regarding the giving of mahar from the perspectives of the Shafi'i and Maliki schools of thought within Islamic jurisprudence. This study seeks to compare the viewpoints of the Shafi'i and Maliki schools regarding the law of mahar in marriage through a deep analysis of fiqh literature, classical scholars' opinions, fatwas, and relevant research. The goal is to understand the differences and similarities between their perspectives and to draw theoretical conclusions regarding their Islamic legal perspectives on mahar within the context of marriage. The analysis reveals that mahar in Islam is a mandatory gift given by the husband to the wife during the marriage contract, serving as a token of appreciation and acceptance of the marriage, as mandated in the Quran. While the Shafi'i and Maliki schools differ in their views on the amount, type, and manner of giving mahar in marriage, they both uphold the principle that mahar is an integral part of Islamic marriage law.